Do I Belong?: Gender, Peer Groups, and STEM Achievement (International Journal of Gender, Science and Technology, 2015)
Women’s underrepresentation in many STEM fields is due to a combination of individual and sociocultural factors. Among these, the peer group is one potentially powerful force reviewed in this article. First, I describe key processes associated with group belonging. The social identities associated with group belonging can shape individuals’ task and interpersonal values. Second, I consider how the values reinforced in many girls’ and women’s peer groups may conflict with their perceptions of STEM. In addition, girls and women may experience rejection and hostility from their male peers regarding STEM achievement. Conversely, when important peer groups value and support STEM, they may validate girls’ and women’s sense of belongingness in STEM fields. Next, I highlight some strategies for reducing peer sexism and foster STEM belonging. Finally, I close with some recommendations for future research.